CATEGORY SHIFTS ANALYSIS IN THE TRANSLATION OF THE TALES OF BEEDLE THE BARD - Adani Nur Sabrina (Jurnal Sosial Humaniora dan Pendidikan, 2022)
In the process of translation, numerous challenges oftentimes emerge due to the differences between the source language and the target language. For each difficulty, there are various translation theories and strategies that can be applied to address them. This research focuses on one of the strategies, namely category shifts as proposed by Catford (1965). The sources of the data used are J.K. Rowling’s The Tales of Beedle the Bard (2008) and its Indonesian translation, Kisah-Kisah Beedle Si Juru Cerita (2009). This research aims to find category shifts in the translation and how they are implemented. The method used in conducting the research is descriptive qualitative and the data are chosen randomly. The result of the research shows that the translation uses all kinds of category shifts with a total of 131 data, which include 33 structure-shifts, 32 class-shifts, 52 unit-shifts, and 14 intra-system-shifts. It is expected that this research can be used by translators as they encounter difficulties related to category shifts, or by future researchers who are willing to conduct similar research.